TINDAK KEKERASAN PADA WANITA PEDAGANG MENGINAP DI PASAR KOTA YOGYAKARTA - Nur Djazifah (LPPM UNY, 2001)
Abstract The objective of this study is to prescribe the profile of woman merchandisers who stay overnight in the market and receive harsh behavior. The data were collected through observation, deep interview both through the subject of the study, and the reliable source persons who are related to the case, e.g. market officers, head (lurah) of pasar, market securities and other woman-merchandiser fellows. The result of the study prescribe that 1) Those woman-merchandisers have experience on harsh behavior in the variety of degrees; 2)Most of them have low educational level, only one woman has a Senior High School diploma, three women have Junior High School diplomas and the rest have Elementary School diplomas and lower; 3) The age of those women varies from 30through over 70 years old; 4) the harsh-behavior types comprise cases of sexual harassment and non-sexual harassment;5)The attackers are buyers, tricycle drivers, car drivers, helpers of the drivers, strangers , their own fellow- merchandisers, drinkers, marker officers and retailers;6)The effects of harsh-behavior attack are various; annoyance, angry, sadness, big deficits, uncertainty, and uneasiness. Even though some do not care;7)Most women merchandisers admit these harsh behavior as their fate;8)They help usually comes from their fellow-merchandisers or closed relatives both in physical help, financial donation, or psychological advice. Keywords: woman merchandiser night stayers, harsh behavior